Ovarian superstimulation with FSH in Wagyu breed bovine donors impacts folicular dynamics but does not improve the amount of embryos (Research, Society and Development, 2021)
The increase of the world population generates the need to raise the production of food of vegetal and animal origin. In Brazil, livestock farming has evolved, demonstrating the important role of the country in the production of food. In this way, researchers of this productive chain have been looking for technologies related to production and reproduction, above all, to the use of reproduction biotechnologies, seeking to increase the production of different bovine breeds. Thus, the objective of this research was to investigate the efficacy of ovarian FSH super stimulation in bovine Wagyu oocyte donor females on follicular dynamics and in vitro embryo production. Twelve Wagyu animals, aged 12 to 24 months, randomly distributed in a crossover design were used in two groups: Group 1= animals not stimulated with FSH and Group 2= animals stimulated with FSH. The follicular, oocyte and embryonic variables were evaluated. It was observed that ovarian overstimulation in Wagyu oocyte donor cows with FSH improved the mean and large follicles but reduced the rate of oocyte recovery and, despite the best percentage of viable oocytes, there was no improvement in the amount of embryos produced in vitro.